China's COVID-19 Control Strategy and Its Impact on the Global Pandemic - Ding, Difeng; Zhang, Ruilian (Frontiers in Public Health, 2022)
Public health crises are challenging for governments and health systems, and coronavirus disease 2019 (COVID-19) has presented huge challenges to humans worldwide. In the context of COVID-19 in China, we explore China's control strategies and challenges. Our analysis examines seven strategies: digital technology pandemic prevention, zero-case policy, all-staff nucleic acid testing, all-staff vaccinations, the long-term quarantine system, and the official accountability system. Additionally, it considers three challenges: repeated pandemic waves, increased downward pressure on the economy and social exhaustion. We identify the causes of these challenges, including social and natural factors, and the controls put in place. We contend that China's control strategies slowed the spread of the global pandemic and that Chinese vaccines have promoted global vaccine equity.